Strengthening Students’ Soft Skills and Moral Character Through Islamic-Based Educational Seminars - Muhimmatul Hasanah; Ahmad Khoirul Umam; Biyati Ahwarumi (Filantropis: Jurnal Pengabdian kepada Masyarakat, 2026)
This community service program aimed to strengthen students’ soft skills and moral character through Islamic-based educational seminars at SMPN 2 Sunan Drajat. The activity addressed students’ limited understanding of self-development, future planning, discipline, and social responsibility in the digital era. The program employed interactive seminar methods, Islamic motivational approaches, discussions, and self-reflection assignments. Seminar materials included self-potential recognition, soft skill development, future planning, and moral character building. The results showed increased student participation and improved understanding of communication skills, discipline, responsibility, and positive moral values. Students were also able to identify their potential and formulate future goals and self-development plans. Overall, the activity contributed to strengthening students’ character, social awareness, and readiness to face future challenges in the school and pesantren environment.